Religion and Families : An Introduction - Marks, Loren D. and Dollahite, David C (New York Routledge, 2017)
This is the first multidisciplinary text to address the growing scholarly connection between religion and family life. The latest literature from family studies, psychology, sociology, and religion is reviewed along with narratives drawn from interviews with 200 racially, religiously, and regionally diverse families which bring the concepts to life. Written in a thought-provoking, accessible, and sometimes humorous style by two of the leading researchers in the field, the book reflects the authors'firsthand experience in teaching today's students about religion's impact on families. Prior to writing the book, the authors read the sacred texts of many faiths, interviewed religious leaders, and attended religious services for a wide array of faiths. The result is an accurate and engaging account of why and how families are impacted by their religion. The pedagogical features of the text include boldfaced key terms defined in the glossary, text boxes, chapter conclusions, summary points, and review questions. Religion and Families: Examines several denominations within Christianity, Judaism, and Islam. Reviews findings from racially and ethnically diverse families, from traditional and diverse family forms, and examines gender and life-course issues. Addresses the impact of one's religious involvement on longevity, divorce rates, and parenting styles. Considers demographic, family-, couple-, and individual-level data that relate to prayer and other sacred practices. Presents a balanced treatment of the latest research and a new model for studying family and religion. Explores the'whys, ''hows, 'and processes at work in the religion-family connection. The book opens with a discussion of why religion and family connections matter. Chapter 2 defines religion and presents a new conceptualization of religion. Empirical research connections between religion and marriage, divorce, family, and parent-child relationships are explored in chapters 3 through 6. The interface between religion and the family in Christianity, Judaism, and Islam are reviewed in chapters 7, 8, and 9. Chapter 10 explores the unique challenges that religion presents for diverse family forms. Prayer as a coping mechanism for life's challenges such as death and disability are explored in chapter 11. Chapter 12 examines forgiveness in the context of marriages and families. The book concludes with a review of the book's most important themes and findings. Intended as a text for undergraduate courses in family and religion, the psychology or sociology of the family, the psychology or sociology of religion, pastoral/biblical counseling, or family and youth ministry, taught in human development and family studies, psychology, sociology, religion, social work, pastoral counseling, and sometimes philosophy. This book also appeals to family therapists and counselors.
Keywords: Families--Religious life -- Marriage--Religious aspects -- Religion -- Parenting -- Religious life